“ABSURDIST” WORLD IN THE SERIES OF NOVELS BY LAJOS GRENDEL NEW HONT - Gizińska, Csilla (Porównania, 2014)
The theme of the paper is the world of selected novels written during the transition by Lajos Grendel, the Hungarian writer from Slovakia (Tömegsír 1999, Nálunk, New Hontban 2001, Mátyás király New Hontban 2005). These positions can be considered in a broad sense as a trilogy taking place in the same fictional town of New Hont and its environs. The author sets the multi-ethnic Central European reality of the period after the regime change in such “absurdist” scenery and points to the irrational and insane logic of the world hitting the margins of history. Grendel outlines the skyline of the national identity and self-esteem disorders, economic mess and political chaos consciously looking at the same time for the most authentic style, language and absurdist literature genres.